The Implementation Gap of the Independent Curriculum Between Urban and Rural School - annisa sucianda (Jurnal Inovasi Pendidikan Nusantara, 2026)
Education has a central role in shaping qualified human resources and supporting a nation’s progress. To improve learning quality, the Indonesian government introduced the Independent Curriculum, which aims to provide a more flexible and student-oriented learning approach. However, its implementation has revealed noticeable differences between urban and rural schools. Urban schools usually benefit from better facilities, access to technology, and more frequent teacher training. In contrast, rural schools still struggle with limited resources, weak infrastructure, and a lack of professional support. This study discusses the main factors causing the inequality in applying the Independent Curriculum between both areas. It also identifies challenges faced by teachers and schools in rural regions and suggests possible solutions to minimize the gap. The results of this study are expected to guide policymakers, educators, and related stakeholders in promoting equal learning opportunities and ensuring that the goals of the Independent Curriculum can be achieved across all parts of Indonesia.